Differential absorption lidar detection of ozone in the troposphere and lower stratosphere - Browell, E. V. (1990)
The DIAL technique for deriving O3 profiles from lidar measurements is discussed. Examples of a variety of O3 and aerosol measurements are presented from studies of (1) photochemically produced O3 in the summertime over the eastern United States and in biomass burning plumes during the dry season over the Amazon Basin of Brazil; (2) vertical O3 transport from the mixed layer into the free troposphere via cloud dynamics and from the stratosphere into the troposphere via tropopause fold events; and (3) O3 depletion in the O3 hole over Antarctica. The NASA airborne DIAL system is considered to be an advanced field system.